MODERNITY AND WAR: ANTHROPOLOGICAL APPROACH IN POLEMOLOGY - A. A. Kravchenko; O. V. Starovoit (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Introduction. To understand the causes of wars and conflicts that, unfortunately, increasingly embrace modern civilization, we need to use a multidisciplinary research approach. The most appropriate study, in this case, is “polemology” which provides multidisciplinary research of the nature and origins of violence. The problem of the mankind salvation, which N. Fedorov attempted to solve in the 19th century, lies in looking for a possibility to realize and change the nature of violence. Theoretical basis. In the study we used a systematic approach to identify the internal relationship between different types of violence and possible ways of violence counteracting. Originality. As a result of the systematization of modern research in polemology, we found that modern science is not able to influence the gene structure of aggression. For this reason, the problem of salvation of the mankind is entrusted to neural programming technologies and educational technologies, based on an anthropological approach. Conclusions. Setting clear boundaries or Rubicon, between coercion and violence (in the meaning of evil) is possible only in cases when mankind gives up its private interests and takes care of the future of the Earth civilization. The problem of the mankind salvation is connected with the existence and realization of the ideas and ideals common for all people of the Earth. It is not the subject of the national safety strategies, which are focused on saving, and development of the national and cultural interests. However, it is a matter of the whole Earth civilization safety which is focused on the “Noosphere” interests and mankind salvation in the situation of its confrontation with the powers of outer space. In comparison with the possible outer space hazards, international and local conflicts, confrontations and wars, lose their priority.